A method for optimizing the lime-sand ratio of layered filling based on regulating layer
By adding a high-gray-sand ratio control layer to the layered filling body and optimizing the relationship between the gray-sand ratio, the problem of layered filling body being filled multiple times when the goaf is large and the middle is easily collapsed, achieving the overall The increase in strength and the reduction in filling costs have improved mining safety.
Patent Information
- Application Number
- CN202410996279.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-24
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-07-24
AI Technical Summary
The existing layered filling method requires multiple fillings when the goaf is large, and the middle of the layered filling body is prone to collapse when returning to the mining column, which affects mining safety.
Add a high ash-sand ratio control layer to the layered filler, and optimize the ash-sand ratio of each layered filler by adjusting the height proportion of the control layer to ensure the overall strength and reduce the filling cost.
By optimizing the relationship between the gray-sand ratio, the overall strength of the layered filling body is improved, the filling cost is reduced, and the mining safety is improved, avoiding the risk of collapse in the middle of the layered filling body.
Smart Images

Figure CN118815536B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of mining and filling, and in particular to a method for optimizing the ash-sand ratio of a layered filling body based on a regulating layer. Background Art
[0002] The empty field subsequent filling method is to divide the ore body into chambers and pillars, first fill the chambers after mining, and then fill again after mining the pillars, with high recovery efficiency. In order to effectively reduce the filling cost, the mine currently adopts layered filling, that is, the upper and lower layers use a high lime-sand ratio, and the middle layer uses a low lime-sand ratio. However, this filling method has the following shortcomings: 1. The volume of the goaf is large and requires multiple fillings to be completed; 2. When the two-step recovery of the pillars is carried out, the middle part of the layered filling body that serves as a temporary pillar is prone to collapse, which not only affects normal mining, but also seriously threatens the safety of on-site workers. Summary of the invention
[0003] The purpose of the present invention is to solve the deficiencies of the prior art and provide a method for optimizing the ash-sand ratio of each layered filling body by adding a regulating layer with a high ash-sand ratio into the layered filling body, thereby reducing the filling cost while ensuring the overall strength of the layered filling body.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] A method for optimizing the lime-sand ratio of a layered filling body based on a regulating layer comprises the following steps:
[0006] Step 1: preparing layered filling body specimens, wherein the layered filling body specimens include two-layered filling body specimens under different lower layer ash-sand ratios and control layer height proportions;
[0007] Step 2: Perform triaxial compression tests on the layered filling body specimens described in step 1 and draw stress-strain curves to obtain the strength, peak strain and failure mode of the specimens;
[0008] Step 3: Calculate the cohesion c and the internal friction angle φ of the layered filling body specimen according to the stress peak value of the stress-strain curve and the Mohr-Coulomb criterion;
[0009] The calculation expressions of the cohesion c and the internal friction angle φ are:
[0010] (1)
[0011] (2)
[0012] Where: , are axial pressure and confining pressure, respectively, in kPa; k is the fitting slope; b is the correlation coefficient;
[0013] Step 4. According to steps 2 and 3, the c and φ values of the specimens under different conditions are calculated. According to the variation law of c and φ values and strength, the relationship between the height setting of the regulating layer of the layered filling body and the corresponding ash-sand ratio of the layer of filling body is obtained to determine the optimal ratio, where the layer refers to the upper layer, the lower layer and the regulating layer.
[0014] Furthermore, the water-cement mass fraction of the two-layered filling body specimen described in step one is 65%, including an upper layer with a cement-sand ratio of 1:6 occupying 1 / 10 of the height of the entire specimen, and a lower layer including a regulating layer occupying 9 / 10 of the height of the entire specimen; the cement-sand ratio of the lower layer including the regulating layer is 1:7, 1:9 or 1:20, respectively, and the cement-sand ratio of the regulating layer located in the middle position of the lower layer including the regulating layer is 1:4, and the height accounts for 0, 1 / 5 or 2 / 5, respectively.
[0015] Furthermore, the specimens with the lower layer ash-sand ratio of 1:9 and 1:20 described in the present invention only have a regulating layer with a height ratio of 2 / 5.
[0016] Furthermore, the confining pressures in the triaxial compression test described in the present invention are 0, 75 kPa, 150 kPa, and 300 kPa, respectively.
[0017] Furthermore, the triaxial compression test described in the present invention adopts a strain-controlled loading mode, with a loading rate of 0.5 mm / min, and the loading is stopped when the specimen is damaged.
[0018] Furthermore, the variation pattern of c, φ value and intensity described in the present invention can be plotted as a variation pattern diagram of c, φ value and intensity.
[0019] Beneficial effects of the present invention:
[0020] The present invention optimizes the relationship between the ash-sand ratios of the stratified filling body and the corresponding layers by adding a regulating layer with a high ash-sand ratio into the stratified filling body and setting the height ratio of the regulating layer. This reduces the filling cost while ensuring the overall strength of the stratified filling body, ensures the safety of on-site workers, and provides a theoretical basis for safe mining of mines. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A schematic diagram of making a layered filling body specimen according to an embodiment of the present invention;
[0022] Figures 2~6 The stress-strain curves of the layered filling body specimens under different conditions in the embodiments of the present invention;
[0023] Figure 7-8 The strength-confining pressure relationship of the specimens under different conditions in the embodiments of the present invention;
[0024] Fig. 9The peak strain-confining pressure relationship of the specimens under different conditions in the embodiments of the present invention;
[0025] Figures 10-11 The failure modes of the test pieces under different conditions in the embodiments of the present invention;
[0026] Fig.12 Schematic diagram of the variation of c and φ values of the test piece under different conditions in the embodiment of the present invention. DETAILED DESCRIPTION
[0027] The content of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0028] The materials of the layered filling specimens used in this implementation are tailings taken from an iron ore filling station in Anhui, 42.5 ordinary Portland cement and ordinary tap water.
[0029] A method for optimizing a layered filling body based on a regulating layer comprises the following steps:
[0030] Step 1: Prepare a layered filling specimen;
[0031] See also Figure 1 , a transparent cylindrical mold with a diameter of D = 39.1mm and a height of H = 80mm was used to make a layered cemented filling body specimen with a water-cement mass fraction of 65%. The specimen was divided into an upper layer, a lower layer and a regulating layer. The ash-sand ratio of the upper layer was 1:6, the ash-sand ratio of the lower layer was 1:7, 1:9, and 1:20, and the ash-sand ratio of the regulating layer was 1:4. The heights of the upper and lower layers accounted for 1 / 10 and 9 / 10 of the entire specimen, respectively. The regulating layer was set in the middle of the entire specimen (i.e., located in the lower filling body), and its height accounted for 0, 1 / 5, and 2 / 5 of the entire specimen height, respectively. For the convenience of comparison, only the regulating layer accounting for 2 / 5 of the specimen height was set in the specimens with a lower ash-sand ratio of 1:9 and 1:20, as shown in Table 1. Referring to the relative height position marked on the mould, pour the slurry of the above proportion in batches, with an interval of 12 hours each time. After completion, put it into a curing box with a temperature range of 20±1℃ and a relative humidity range of 95±5% for curing. Take it out and demould it after 24 hours, then put it back into the curing box for secondary curing until it reaches the preset age of 28 days, then take it out and immediately perform a triaxial compression test on it.
[0032] Table 1 Height proportion and lime-sand ratio of layered filling specimens made under different conditions
[0033]
[0034] Step 2: Perform triaxial compression tests on the layered filling body specimens described in step 1, with confining pressures of 0, 75, 150, and 300 kPa, respectively, and draw stress-strain curves to obtain the strength, peak strain, and failure mode of the specimens;
[0035] See also Figures 2~6 The specimen numbers in the chart are named in the form of "lower layer ash-sand ratio - control layer ratio" (the same below). Figures 2~4 At the initial stage of loading, when the proportion of the control layer remains unchanged, as the lime-sand ratio of the lower layer increases, the stress-strain curve of the specimen becomes more and more close to a linear growth; see Figure 4 When the proportion of the control layer is 0, the upward concave trend of the curve becomes more obvious as the confining pressure increases; see Figures 4 to 6 , when the proportion is not 0, as the proportion increases, the concave degree of the curve decreases and gradually tends to be consistent. As the load continues to increase, the curve amplitude decreases and becomes convex. At this time, the specimen is in the yield stage. Figures 4 to 6 , the lower layer lime-sand ratio remains unchanged, and when the confining pressure is 0, the initial yield stage of the specimen is not obvious regardless of whether the regulating layer is added or not; Figure 4 When the confining pressure is not 0 and no regulating layer is added, the specimen enters the initial yield stage, and the curve first appears an "inflection point", then the curve rises and enters the yield stage for the second time, until the second "inflection point", i.e., the peak point, appears. Figures 5 and 6 When the regulating layer is added, the initial yield stage of the specimen increases significantly, and the strain hardening trend between the two "inflection points" decreases. Figures 2~4 , when the regulating layer remains unchanged and the confining pressure is 0, an obvious "double peak point" phenomenon appears only when the lower layer ash-sand ratio is low. The specimen is destroyed after the peak, and the curve drops, but it still has a high residual strength. With the increase of the lower layer ash-sand ratio, the post-peak stress drop amplitude of the specimen decreases, and the post-peak ductility characteristics are enhanced. The lower layer ash-sand ratio remains unchanged, and with the increase of the confining pressure, the increase in the residual strength of the specimen with the added regulating layer is greater. This shows that the greater the confining pressure, the better the effect of adding the regulating layer on enhancing the residual strength of the filling body.
[0036] See also Figure 7 It can be seen that the increase of confining pressure and regulating layer improves the strength of the specimen. Under the confining pressure conditions of 0kPa and 300kPa, with the increase of the proportion of regulating layer, the strength increase of the filling body is not much different and is relatively stable; under the confining pressure conditions of 75kPa and 150kPa, the strength increase of the filling body is greatly increased; with the increase of confining pressure, the strength increase of the specimen decreases overall. The strength increase of the 1:7-0 specimen is 26.72%, 12.01%, and 7.78%, showing a gradually decreasing trend, while the increase of the 1:7-1 / 5 and 1:7-2 / 5 specimens is 22.12%, 11.8%, 20.52% and 46.46%, 10.52%, 12.02%, respectively, showing a trend of first decreasing and then increasing. It shows that in the lower confining pressure range (0~75kPa), the filling body without adding regulating layer has a better strength enhancement effect, while in the higher confining pressure range (75~300kPa), the filling body with adding regulating layer has a better strength enhancement effect.
[0037] See also Figure 8 The 1:7-0 specimen in the figure is made according to the actual proportion of a certain iron ore filling station. Taking the strength of the 1:7-0 specimen as a reference, it can be found that under different confining pressures, the difference ratios of the strength of the 1:20-2 / 5 and 1:9-2 / 5 specimens are 2.22%, -7.58%, -4.56%, 5.67% and 9.8%, 23.6%, 17.32%, 15.93%, respectively, and the average values are -0.83% and 16.66%, respectively. The above results show that the strength of the 1:20-2 / 5 specimen is not much different from that of the 1:7-0 specimen. When a certain iron mine performs on-site layered filling and uses a filling slurry with a lime-sand ratio of 1:7 to fill the lower layer of the goaf, it can be replaced by a combination of a lime-sand ratio of 1:20 and a partial lime-sand ratio of 1:4. The 1:20-2 / 5 specimen uses relatively less cement, which is about 2.4% less than the 1:7-0 specimen, and the lime-sand content of the regulating layer is higher, which enhances the overall stability of the layered filling body. When acting as a pillar to support the goaf, it reduces the impact of mining disturbance on the collapse of the middle part of the filling body. The method of the present invention effectively reduces the filling cost and improves the safety of the work site.
[0038] See also Fig. 9 It can be seen that with the increase of confining pressure, proportion of regulating layer and lower layer lime-sand ratio, the peak strain of the specimen increases; when the confining pressure is 0 and the lower layer lime-sand ratio remains unchanged, the change of the proportion of regulating layer has little effect on the peak strain of the specimen.
[0039] See also Figures 10-11 It can be seen that under triaxial compression conditions, when no control layer is added, the layered filling body mainly exhibits shear failure, and after adding the control layer, it mainly exhibits three forms of tensile, shear and mixed failure. When the confining pressure is 0, the failure crack of the 1:7-0 specimen is a single oblique shear crack, and with the increase of confining pressure, the shape of the shear crack changes to "V" and "Y" shapes; the failure crack of the 1:7-1 / 5 specimen is a single transverse shear crack, and with the increase of confining pressure, the transverse shear crack changes to an oblique and "Y" shape, and the failure crack of the 1:7-2 / 5 specimen is a mixed crack of transverse shear and tension, and with the increase of confining pressure, the tensile crack passes through the transverse shear surface (the interface between the control layer and the lower layer), and continues to extend through the upper transverse shear surface, forming a tensile crack that runs through the entire specimen. When the proportion of the regulating layer remains unchanged at 2 / 5 and the confining pressure is 0, the destructive cracks of the 1:20-2 / 5 specimen are mainly shear cracks with a smaller inclination angle, accompanied by multiple secondary shear cracks. When the confining pressure is 75 kPa, two transverse shear cracks are dominant, and when the confining pressure is 150 and 300 kPa, two transverse shear cracks and tensile cracks running through the shear surface are dominant. The failure mode of the 1:9-2 / 5 specimen changes with the increase of confining pressure in an almost opposite manner to that of the 1:7-2 / 5 specimen. When the confining pressure is low, two transverse shear cracks and tensile cracks running through the upper part of the specimen are dominant, while when the confining pressure is high, transverse shear cracks and tensile cracks in the middle and lower parts are dominant.
[0040] Step 3: Calculate the cohesion (c) and internal friction angle (φ) of the layered filling specimen according to the stress value and Mohr-Coulomb criterion obtained in step 2;
[0041] Using the data obtained from the triaxial test, the c and φ values of the layered filling body can be obtained by linear fitting according to the Mohr-Coulomb criterion. The fitting relationship is y=kx+b (where y is ; x is ; , are axial pressure and confining pressure respectively; k and b are correlation coefficients), and the fitting results are shown in Table 2. The calculation formulas for c and φ values obtained from the fitting relationship are as follows:
[0042] (1)
[0043] (2)
[0044] Combining formula (1) and Table 2, the variation law of c and φ values of the specimens under different conditions is shown in Fig.12 When the proportion of the regulating layer remained unchanged, as the lower layer ash-sand ratio increased from 1:20 to 1:7, the c value of the specimen increased by 22.89 kPa and 2.71 kPa, and the φ value increased by 1.8° and 5.9°, respectively; when the lower layer ash-sand ratio was 1:7, as the proportion of the regulating layer increased from 0 to 2 / 5, the c value of the specimen increased by 6.27 kPa and 17.1 kPa, and the φ value increased by 4° and 5.5°, respectively. It can be seen that the c and φ values are positively correlated with the lower layer ash-sand ratio of the filling body and the proportion of the regulating layer. By comparing specimen 1:7-0 with specimen 1:20-2 / 5, it was found that the difference in c value between the two was small, only 2.23 kPa (1.09%), and the φ value differed by 1.8° (9.23%). It was further determined that the control layer combination of a lime-sand ratio of 1:20 and a lime-sand ratio of 1:4 could be used instead of the lower layer lime-sand ratio of 1:7 to achieve the purpose of saving filling costs and improving operation safety.
[0045] Table 2 Fitting results
[0046]
[0047] Step 4: According to step 2 and step 3, the c and φ values of the specimens under different conditions are calculated. According to the variation law of c and φ values and strength, the relationship between the height setting of the regulating layer of the layered filling body and the corresponding ash-sand ratio of the filling body of the layer is obtained to determine the optimal ratio, where the layer refers to the upper layer, the lower layer, and the regulating layer. To determine the optimal ratio, the 1:20-2 / 5 sample and the 1:7-0 sample prepared according to the actual filling ratio of a certain iron ore are taken as examples. Whether in terms of strength, deformation characteristics, c and φ values, or failure mode, the two are not much different. The feasibility of 1:20-2 / 5 replacing 1:7-0 filling body is theoretically determined, which provides certain theoretical guidance for saving filling costs and improving operation safety in mines.
[0048] The above-described embodiments are merely descriptions of preferred embodiments of the present invention, and are not limitations on the protection scope of the present invention. Without departing from the design spirit of the present invention, various equivalent modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field all fall within the protection scope of the present invention.
Claims
1. A method for optimizing the lime-sand ratio of layered filling based on a regulating layer, characterized in that: The following steps are involved: Step 1: Prepare a layered filling body specimen, wherein the layered filling body specimen includes two-layered filling body specimens under different lower layer lime-sand ratios, different control layer height proportions, and different control layer lime-sand ratios; the control layer is arranged in the middle of the lower layer; Step 2: Perform triaxial compression tests on the layered filling body specimens described in step 1 and draw stress-strain curves to obtain the strength, peak strain and failure mode of the specimens; Step 3: Calculate the cohesion c and internal friction angle of the layered filling specimen according to the stress peak value of the stress-strain curve obtained in step 2 and the Mohr-Coulomb criterion. value; The cohesion c and the internal friction angle The calculation expression is: Where: σ1, σ3 are axial pressure and confining pressure respectively, in kPa; k is the fitting slope; b is the correlation coefficient; Step 4: According to Step 2 and Step 3, the c and value, and according to c, The relationship between the height setting of the regulating layer of the layered filling body and the corresponding ash-sand ratio of the layer of filling body is obtained based on the changing law of the value and strength, and the optimal ratio is determined. The layer refers to the upper layer, the lower layer and the regulating layer.
2. The method for optimizing the lime-sand ratio of layered filling based on the regulating layer according to claim 1 is characterized in that: The water-cement mass fraction of the two-layered filling specimen described in step one is 65%, including an upper layer with a ash-sand ratio of 1:6 accounting for 1 / 10 of the height of the entire specimen, a lower layer and a regulating layer accounting for 9 / 10 of the height of the entire specimen; the ash-sand ratio of the lower layer is 1:7, 1:9 or 1:20, the ash-sand ratio of the regulating layer is 1:4, and the height accounts for 0, 1 / 5 or 2 / 5 respectively.
3. The method for optimizing the lime-sand ratio of layered filling based on the regulating layer according to claim 2 is characterized in that: The specimens with the lower layer ash-sand ratio of 1:9 and 1:20 were only provided with a regulating layer with a height ratio of 2 / 5.
4. The method for optimizing the lime-sand ratio of layered filling based on the regulating layer according to claim 1 is characterized in that: The confining pressures in the triaxial compression test described in step 2 are 0, 75 kPa, 150 kPa, and 300 kPa, respectively.
5. A method for optimizing the lime-sand ratio of layered filling based on a regulating layer according to any one of claims 1 to 4, characterized in that: The triaxial compression test described in step 2 adopts a strain-controlled loading mode with a loading rate of 0.5 mm / min, and the loading is stopped when the specimen is damaged.
6. The method for optimizing the lime-sand ratio of layered filling based on the regulating layer according to claim 5 is characterized in that: In step 4, a change law diagram is drawn to obtain c, The law of change of value and intensity.